Models for teaching mathematical courses and research variables that were based on Arab educational researches within the general education stage - Alotaibi, Salman Sahud (Journal of Educational and Psychological Sciences, 2021)
The study aimed at identifying models for teaching mathematical courses that were based on a sample of Arab educational researches in the field of teaching and learning of mathematics, applied to the general education stage. In order to contribute to their identification and classification in a way that helps the scientific efforts and classify them according to the objectives of the models and their research variables that, have been connected to. The content analysis of the research contributions was limited to what was presented during the period between 2005-2020, within the Arab informational publishing vessels, while examining the research topics and their methodologies in a random sample of (123) studies. The results revealed the large number of research studies, which focused on Bybee model "quadruple and pentagram constructive learning" and the learning dimensions model for Marzano. The research contribution has also decreased in a number of models, such as self-organized education, case-based reasoning model and Lesh model. Most of the research studies have adopted the experimental method, with their focus on the variables of achievement and mathematical thinking. The study recommended making use of mathematics teaching models, with adopting developmental and evaluation methodologies, and proposing teaching models for mathematical courses, in order to achieve deepening learning and support for understanding and scientific application processes.
Keywords: Teaching Models; Mathematics Teaching; Teaching Strategies; Curriculum Development